The being and the essence since Thomas Aquinas and Francisco Suárez: Between realism and idealism? - Yangali Núñez, Oscar Edmundo (2022)
In this article I propose that the notions of being and essence according to Aquinas and Suárez are different ways of conceiving the contingency of entities, but not mutually exclusive conceptions. On the contrary, I consider that, Aquinas by putting the emphasis of being on the extramental while Suárez on the intelligible, push us to find a common ground to avoid the extremes of naïve realism and idealism. First, I analyze the notions of potency and act in Aquinas and Suárez. Second, I develop its impact on the distinction between being and essence. Finally, I compare both metaphysics to better delimit our consideration of the real, both in the extramental and conceptual spheres.